Precise Measurement of Carbon Concentration and Isotopic Ratios in Silicate Rocks by a High Sensitivity Elemental Analyzer Coupled with a Continuous Flow Isotope Mass Spectrometry - ZHA Xiang-ping; GONG Bing; ZHENG Yong-fei (Yankuang ceshi, 2017)
The precise and accurate analyses of minor carbon in silicate rocks can provide valuable insights into the origin of fluid and formation processes. The Elemental Analyzer-Isotope Ratio Mass Spectrometry (EA-IRMS) is a quick analytical method using small quantities of sample. In this study, EA-IRMS is applied to analyze carbon isotopic composition of trace carbon in silicate rock. Based on a series of tests, the key analytical parameters are confirmed. The normalization procedure and reference materials selection are as follows. ① Selection of standard materials with a wide carbon isotope composition range and reasonable carbon isotope distribution. Preparation of the mixtures of reference materials and super quality quartz power. ② A calibration curve was established using the measured values and certified values of the three reference materials similar to the samples. The measurement of natural samples is normalized to achieve an accurate determination of trace carbon content as low as 600 μg/g in silicate rocks and carbon isotopic composition. National standard material GBW04416 is used as an unknown sample to test the linear equations regressed with different contents. When the carbon content is no lower than 600 μg/g, the standard deviations are 0.02‰, 0.04‰, 0.05‰, -0.07‰, 0.11‰, respectively. For the mixture of MERCK and USGS24, the determined carbon isotopic composition and carbon content are comparable with the true value within analytic uncertainty. Therefore, the high precision and accuracy of carbon isotopic composition can be obtained for carbon content no less than 600 μg/g in 30 mg silicate rock. The carbon content of the sample was established based on the linear curve established by the peak area (peak intensity) of the standard mixture of different carbon contents and the corresponding content. Analytic uncertainty of carbon content of the sample is within 10%.